Islamic religious education and the internalization of religious moderation values among students: Literature review - Anhar; Irsyadunnas; Muhamat Khoirisun; Makhrus Ali; Siti Afifatun (At Turots: Jurnal Pendidikan Islam, 2025)
This study analyzes the internalization of religious moderation values in Islamic education through a systematic literature review of 15 scientific publications from 2021-2025. Religious moderation in Islamic education context represents a multidimensional construct integrating socio-religious, cultural, and practical implementation aspects. Findings reveal that value internalization requires multifaceted strategies including structured learning programs, extracurricular activities, school environment optimization, and inclusive religious activities. Educational leadership quality and teachers' pedagogical competence serve as mediators in the relationship between moderation curriculum and tolerant character formation. Religious moderation implementation shows varying effectiveness: elementary education 75%, secondary 80%, and higher education 85%. Local socio-cultural contextual factors moderate the effectiveness of internalization programs. Critical thinking development, pedagogical reform, and digital technology integration become crucial elements in realizing moderate Islamic education responsive to contemporary radicalism challenges.